2014
DOI: 10.5194/bg-11-5235-2014
|View full text |Cite
|
Sign up to set email alerts
|

Australian net (1950s–1990) soil organic carbon erosion: implications for CO<sub>2</sub> emission and land–atmosphere modelling

Abstract: Abstract. The debate remains unresolved about soil erosion substantially offsetting fossil fuel emissions and acting as an important source or sink of CO 2 . There is little historical land use and management context to this debate, which is central to Australia's recent past of European settlement, agricultural expansion and agriculturallyinduced soil erosion. We use "catchment" scale (∼ 25 km 2 ) estimates of 137 Cs-derived net (1950s-1990) soil redistribution of all processes (wind, water and tillage) to ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 46 publications
(62 reference statements)
0
12
0
3
Order By: Relevance
“…A global N deposition model product from 1860 to 2100 offers dynamic forcing variables for coupled C-N models [Lamarque et al, 2010]. Simulating horizontal and vertical movements caused by soil erosion at regional and global scales will require a global net soil redistribution map [Chappell et al, 2014] to provide boundary conditions for global land models.…”
Section: Representation Of External Variables In Esmsmentioning
confidence: 99%
“…A global N deposition model product from 1860 to 2100 offers dynamic forcing variables for coupled C-N models [Lamarque et al, 2010]. Simulating horizontal and vertical movements caused by soil erosion at regional and global scales will require a global net soil redistribution map [Chappell et al, 2014] to provide boundary conditions for global land models.…”
Section: Representation Of External Variables In Esmsmentioning
confidence: 99%
“…There are a few studies involving techniques of quantitative measurement of SOC/TC transported by erosion from a watershed or a well-demarcated area. In Australia, Chappell et al [25] estimated the magnitude of 137 Cs -derived redistribution of SOC by all processes (water, wind, and tillage) at 4 Tg SOC/yr for 1950-1990s. This represents an average loss of 2% of TC stock, assuming that total C is mineralized as CO 2 , and would represent a net national flux of 15 Tg CO 2 eq/yr from all C pools in Australia.…”
Section: Country/region Study Duration (Yr) Soc Erosion Erosion Typesmentioning
confidence: 99%
“…By credibly accounting for the effects of erosion on net C exchange between the soil and the atmosphere, it may be possible to identify global hot spots of undertaking targeted interventions to mitigate the erosion-induced positive feedback to global warming. In Australia, Chappell et al [25] found SOC erosion by all processes at 4 Tg/yr. (or 2% of total C stock in 10-cm depth).…”
Section: Implications Of Ignoring Erosion Induced Transport Of Carbonmentioning
confidence: 99%
“…Using remote-sensing observations, Ginoux et al (2012) estimated that anthropogenic windblown dust sources account for 75 % of emissions in Australia and 25 % globally. Windblown dust emissions from cropland is of global importance (Mendez and Buschiazzo, 2010;Singh et al, 2012;Wang et al, 2013;Chappell et al, 2014;Xi and Sokolik, 2016).…”
Section: Introductionmentioning
confidence: 99%